MANFAAT ICT SEBAGAI MEDIA PEMBELAJARAN DI SD DHARMAJAYA PALEMBANG - Ade Afni Utari; Syafwatul Putria Hidayatullah (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This study aims to determine the benefits of Information and Communication Technologies (ICT) or more often we know Information and Communication Technology (ICT) as a learning media. ICT is a media or tool that is used to balance technological progress. This research method uses Qualitative Methods. data collection techniques with triangulation (combined). With the use of ICT that is effective and efficient, attractive, optimal, and stimulates the creativity of students, ICT is one of the learning media that is widely used in various fields of education because it increases effectiveness and efficiency in the learning process.